Search for the standard model Higgs boson in the $H$ to $Z Z$ to $\ell \ell τ τ$ decay channel in $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2272 authors) (2012)
A search is reported for the standard model Higgs boson in the decay mode H to ZZ to tau plus lepton pairs, where the leptons are either electrons or muons, in proton-proton collisions at sqrt(s)=7 TeV, corresponding to an integrated luminosity of 4.7 inverse femtobarn collected with the CMS detector at the LHC. No evidence is found for a significant deviation from the background expectation. An upper limit four to twelve times larger than the predicted value is set at 95% confidence level for the product of the standard model Higgs boson production cross section and decay branching fraction in the mass range 190 < m(H) < 600 GeV.